(untitled) (Contemporary Mathematics, 2024)
This paper recovers dark-singular straddled optical solitons for the dispersive concatenation model with power-law of self-phase modulation using the tanh-coth approach. The individual dark or singular solitons are not supported by the model for power-law unless this law collapses to Kerr law as proven with the usage of undetermined coefficients, earlier.